Hukum Islam: Dialektika Konsep Ta’abbudi dan Ta’aqquli - Abd Basir; Fitriyani Fitriyani (Jurnal Ilmiah AL-Jauhari: Jurnal Studi Islam dan Interdisipliner, 2022)
This paper aims to find out the concept of ta'abbudi and ta'aqquli in Islamic law, Ta'abbudi which is interpreted as a religious understanding that must be followed without having to question the reasons behind a religious sharia commandment. Meanwhile, ta'aqquli which is interpreted as a religious understanding that is born from the spirit of Islamic law is revealed. The method used in this study is based on a literature review. The data collected is based on the search for several documents, literature, scientific journals related to the context of this study. The analysis was done descriptively. The results of the study found that Ta'abbudi is absolute, static, and its existence is not based on mere outward benefit, while ta'aqquli is relative, not static, and its existence is based on the benefit of humans so that it is rational. However, every ta'aqquli must contain the values ​​of worship. On the other hand, every ta'abbudi contains benefits for humans. These two concepts have contributed greatly to the development of Islamic law